Chemoprotective Effect of Leaf Extracts of Cecropia distachya Huber (Urticaceae) in Mice Submitted to Oxidative Stress Induced by Cyclophosphamide - Luiz, Tatiane Cordeiro; Rialto, Luiz Henrique; de Moura, Fernando Rafael; Aguiar, Danilo Henrique; Sugui, Marina Mariko; Bicudo, Rogério de Campos; Sinhorin, Adilson Paulo; Sinhorin, Valéria Dornelles Gindri (Fronteira: Journal of Social, Technological and Environmental Science, 2020)
The objective of this work was to evaluate the chemoprotective effects of the embaúba Cecropia distachya Huber (two methanolic fractions: F1 and F2) on oxidative stress induced by cyclophosphamide (75 mg kg-1) in mice, as well as phytochemical analyzes by LC-MS/MS. In the experimental model, the fractions increased the hepatic and cardiac catalase (CAT), reduced glutathione (GSH) of the kidney and the heart. F1 increased platelet levels (PLT), hemogram (RBC), hematocrit (HCT) and hemoglobin (Hb) and F1 reduced hepatic lipid peroxidation (TBARS) and aspartate aminotransferase (AST) activity increased. F1 was attributed to possible hypoglycemic activity and possible immunosuppressive effects and F2 presented antimutagenic activity. In some cases, the fractions were also hepatotoxic. These results demonstrated that the fractions stimulate the antioxidant defenses, being hypoglycemic (F1) and antimutagenic (F2), and, the harmful effects attributed to the fractions may be the association of compounds that were not elucidated in this work.